Pengaruh Brand Image, Brand Awareness Dan Brand Trust Terhadap Brand Loyalty Konsumen Air Mineral Merek Aqua Pada Mahasiswa Universitas Muhammadiyah Surakarta - Prasetya, Diar Skriptian Eko, Kussudiyarsana, S.E., M.Si (2016)
This aims of this study is to determine the effect of brand image, brand awareness ,and brand trust toward brand loyalty of bottled water products brand AQUA. This research is quantitative. This research is conducted on consumers of bottled water brand AQUA in Muhammadiyah University of Surakarta students. Sample in this research were 100 respondents using probability sampling approach with random sampling method. The type of data in this study using primary data obtained from the respondents through questionnaires that distributed to students of Muhammadiyah University of Surakarta. Testing the instrument in this study using validity and reliability test which aims to determine the feasibility of a question in the questionnaire. Analysis of the data in this study using multiple linear regression analysis is reinforced by the classical assumption test and permanence test models. Results from this study showed that the variable of brand image, brand awareness, and brand trust have a positive and significant effect on brand loyalty variable. These result it can be concluded that the brand image, brand awareness, and brand trust is needed to create brand loyalty in purchasing bottled mineral water brand AQUA in Muhammadiyah University of Surakarta students. Keywords: Brand Loyalty, Brand Image, Brand Awareness, Brand Trust.